2015
DOI: 10.1590/0102-311x00130814
|View full text |Cite
|
Sign up to set email alerts
|

Domínios de atividade física e escolaridade em São Paulo, Brasil: estudo transversal seriado, 2003 e 2008

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
3
9
0
6
Order By: Relevance
“…The emergence of new technologies brings the need to reflect upon the influence of these activities on the attitudes toward PA, since adolescents with higher purchasing power have more access to electronic devices. 28 Finally, it was found that maternal education did not seem to affect enjoyment and preference for PA in both sexes, similar to the findings of Barr-Anderson et al 10 Although adults with higher education tend to be more physically active 29 and that this behavior might influence the habits and attitudes of their children, 30 we again suppose that the perception of psychosocial aspects is probably influenced by other factors not assessed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The emergence of new technologies brings the need to reflect upon the influence of these activities on the attitudes toward PA, since adolescents with higher purchasing power have more access to electronic devices. 28 Finally, it was found that maternal education did not seem to affect enjoyment and preference for PA in both sexes, similar to the findings of Barr-Anderson et al 10 Although adults with higher education tend to be more physically active 29 and that this behavior might influence the habits and attitudes of their children, 30 we again suppose that the perception of psychosocial aspects is probably influenced by other factors not assessed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…9 In general, physical activity is an important factor for health promotion, directly implicating the reduction of mortality and/ or prevalence and later onset of chronic non--communicable diseases, being considered as a determinant for longevity. 10 However, despite being ease for one to practice it and the knowledge about the health benefits of physical activity, the prevalence of physical inactivity among the population is higher in the elderly and tends to increase with age.…”
Section: 456mentioning
confidence: 99%
“…Os testes realizados com o modelo indicaram que os padrões temporais da prática de atividade física no lazer e dos níveis de intenção se assemelharam aos reportados na literatura (BULL et al, 2001;CRUZ, 2015;DUMITH;GIGANTE;DOMINGUES, 2007;JUNEAU;POTVIN, 2010;KEARNEY et al, 1999;KNUTH;HALLAL, 2009;LAFORGE et al, 1999;MIELKE et al, 2014;NUNES et al, 2015;ROMÁN-VIÑAS et al, 2007;SILVA et al, 2014;CHAUDHURY, 2008) SALLIS et al, 2006). Ainda quanto à revisão da literatura sobre o ambiente físico construído, é necessário destacar que as revisões sistemáticas de estudos quantitativos (ARANGO et al, 2013;BANCROFT et al, 2015;BAUMAN et al, 2012;HUMPEL;OWEN;LESLIE, 2002;KACZYNSKI;HENDERSON, 2007;PEARCE;MADDISON, 2011;VAN HOLLE et al, 2012;WENDEL-VOS et al, 2007) relataram uma grande quantidade de resultados originais não significativos, tamanhos de efeito não mais do que modestos e uma alta heterogeneidade metodológica na operacionalização e mensuração dos atributos ambientais e da atividade física.…”
Section: Discussionunclassified
“…Isso pode ter ocorrido porque, em média, as pessoas tiveram mais contatos com outras pessoas que não praticavam atividade física no lazer, já que a proporção populacional era normalmente menor do que 50% nos cenários investigados. Esse, no entanto, é um cenário comum em diversas localidades (CRUZ, 2015;JUNEAU;POTVIN, 2010;MIELKE et al, 2014;NUNES et al, 2015;ROMÁN-VIÑAS et al, 2007;SILVA et al, 2014;CHAUDHURY, 2008), o que serve de alerta ao se planejar campanhas de promoção da atividade física no lazer que utilizem o ambiente social como um dos elementos da ação. (CRUZ, 2015;JUNEAU;POTVIN, 2010;MIELKE et al, 2014;NUNES et al, 2015;ROMÁN-VIÑAS et al, 2007;SILVA et al, 2014;CHAUDHURY, 2008)…”
Section: Uso E Validade Do Modelo Baseado Em Agentesunclassified
See 1 more Smart Citation